Quantum Stochastic Model for Spin Dynamics in Magnetic Systems (Communications in Computational Physics, 2019)
We develop a numerical model that reproduces the thermal equilibrium andthe spin transfer mechanisms in magnetic materials. We analyze the coherent two-particle spin exchange interaction and the electron-electron collisions. Our study isbased on a quantum atomistic approach and the particle dynamics is performed byusing a Monte Carlo technique. The coherent quantum evolution of the atoms is interrupted by instantaneous collisions with itinerant electrons. The collision processesare associated to the quantum collapse of the local atomic wave function. We showthat particle-particle interactions beyond the molecular field approximation can be included in this framework.Our model is able to reproduce the thermal equilibrium and strongly out-of-equilibrium phenomena such as the ultrafast dynamics of the magnetization in nanomaterials.